The genetic landscape of programmed death ligand‐1 (PD‐L1) alterations in head and neck cancer. Issue 3 (17th May 2017) - Heineman, Thomas E.; Widman, Adam; Kuan, Edward C.; St John, Maie
Abstract : Objectives: Nivolumab has recently been shown in the phase III clinical trial CheckMate‐141 to have superior survival rates compared to the current standard of care chemotherapy for recurrent or metastatic platinum‐resistant head and neck squamous cell carcinoma (HNSCC). Nivolumab targets the immune inhibitory receptor programmed cell death 1 (PD‐1). Programmed cell death ligand 1 (PD‐L1) genomics have been poorly characterized in the context of HNSCC, including expression levels of PD‐L1 in individual tumors as well as related up or down‐regulated genes that might function as co‐targets. Study Design: Data mining of The Cancer Genome Atlas (TCGA) Methods: 530 patients with HNSCC were pulled from the TCGA using cBioPortal. Primary tumor site data was available in 279 of the samples (52.6%), of which oral cavity was the most common site (61.6%) followed by larynx (25.8%). Other PD‐1‐sensitive tumors were analyzed to compare PD‐L1 expression in HNSCC relative to other tumors including bladder, renal cell carcinoma, melanoma, and lung carcinomas. Results: A significant fraction of HNSCC tumors have genetic alterations in PD‐L1 (6.2%). HNSCC has the highest PD‐L1 expression of all of the tumor types examined, with a median 60‐fold increase. Several important genes were identified in this study including Caspase 7, ZFYVE9, and Plg‐R(KT) that have a strong relationship with alterations in PD‐L1. Conclusion: In light of the role of PD‐1 and PD‐L1 as key immunotherapy targets in HNSCC, several potential co‐targets identified in this study warrant further investigation. Further, while the number of genetic alterations were small in head and neck carcinomas, alterations in PD‐L1 expression were highly significant. Level of Evidence: NA